WORKSHOP ACTIVITIES IN IMPROVING TEACHER COMPETENCIES TO DEVELOP AN EDUCATIONAL UNIT LEVEL CURRICULUM (KTSP) AT TK PERTIWI DUMAI - Aida Aida (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper is based on the teachers’ low-ability in teacher competencies to develop a curriculum of the educational unit level (KTSP) at TK Pertiwi Dumai. Hence, it needs action to overcome this problem through workshop activities. Based on the description of the background, identification, and limitation of the problem, the focus of the research is related to teacher ability improvement in teacher competencies to develop a curriculum at the educational unit level (KTSP). Therefore, the formulation of the research problem is to see whether there is an improvement in teacher ability of their competencies to compile the educational unit level (KTSP) curriculum through workshop activities at TK Pertiwi Dumai or not. In accordance with the background and formulation of the problem, this paper focuses on the implementation of workshop activities that can improve teachers’ abilities in teacher competencies to develop the educational unit level (KTSP) curriculum at TK Pertiwi Dumai. Type of the research is school action research (PTS). Based on the analysis and discussion, it can be concluded that the teacher's ability in developing the educational unit level (KTSP) curriculum can be improved through workshop activities at TK Pertiwi Dumai. Thus, the teacher acceptance rate increased. The results of comparison aspects of the teacher's ability in developing the educational unit level (KTSP) curriculum through workshop activities from cycle I 58% to cycle II 94% increased.